#TITLE_ALTERNATIVE# - GUNAWAN , GUNTUR
Let F, G dan H be graphs. The notation F ! (G;H) means that any red-blue coloring of the edges of F contains a red subgraph G or a blue subgraph H. Graph F is called a Ramsey (G;H)minimal graph if it satisfies that F ! (G;H) and F fie9(G;H) for any e 2 E(F). The notation Â(G;H) is the class of all Ramsey (G;H)minimal graph. In this Final Project we derive some necessary conditions of graphs belong to Â(P3;P5). From these conditions, we determine some graphs containing a cycle which belong to Â(P3;P5).